Current Status of Training and Certification for Congenital Heart Surgery Around the World: Proceedings of the Meetings of the Global Council on Education for Congenital Heart Surgery of the World Society for Pediatric and Congenital Heart Surgery. Issue 3 (May 2021) - Tchervenkov, Christo I.; Herbst, Claudia; Jacobs, Jeffrey P.; Al-Halees, Zohair; Edwin, Frank; Dearani, Joseph A.; Finucane, Kirsten; Sandoval, Nestor; Sarris, George E.; Fragata, Jose; Abdulgani, Hafil B.; Arboleda, Miguel; et al.
The optimal training of the highly specialized congenital heart surgeon is a long and complex process, which is a significant challenge in most parts of the world. The World Society for Pediatric and Congenital Heart Surgery (WSPCHS) has established the Global Council on Education for Congenital Heart Surgery as a nonprofit organization with the goal of assessing current training and certification and ultimately establishing standardized criteria for the training, evaluation, and certification of congenital heart surgeons around the world. The Global Council and the WSPCHS have reviewed the present status of training and certification for congenital cardiac surgery around the world. There is currently lack of consensus and standardized criteria for training in congenital heart surgery, with significant disparity between continents and countries. This represents significant obstacles to international job mobility of competent congenital heart surgeons and to the efforts to improve the quality of care for patients with Congenital Heart Disease worldwide. The purpose of this article is to summarize and document the present state of training and certification in congenital heart surgery around the world.